1989
DOI: 10.1007/bf02389812
|View full text |Cite
|
Sign up to set email alerts
|

The effects of specificity of training on rating of perceived exertion at the lactate threshold

Abstract: To determine the effects of cycle and run training on rating of perceived exertion at the lactate threshold (LT), college men completed a 40-session training program in 10 weeks (n = 6 run training, n = 5 cycle training, n = 5 controls). Pre- and post-training variables were measured during graded exercise tests on both the bicycle ergometer and treadmill. ANOVA on the pre- and post-training difference scores resulted in similar improvements in VO2max for both testing protocols, regardless of training mode. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
21
0

Year Published

1993
1993
2012
2012

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(25 citation statements)
references
References 24 publications
4
21
0
Order By: Relevance
“…Mahon et al (1998) showed that RPE at VT was 11.5Ϯ2.6 during pedaling for adults. Thus, it could be said that our speculations regarding the exercise intensities at each stage from viewpoint of BLa and RPE are not so far from the previous studies (Boutcher et al, 1989;Mahon et al, 1998;Purvis and Cureton, 1981).…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Mahon et al (1998) showed that RPE at VT was 11.5Ϯ2.6 during pedaling for adults. Thus, it could be said that our speculations regarding the exercise intensities at each stage from viewpoint of BLa and RPE are not so far from the previous studies (Boutcher et al, 1989;Mahon et al, 1998;Purvis and Cureton, 1981).…”
Section: Discussionmentioning
confidence: 67%
“…Regarding the RPE, it was 11.5Ϯ1.1 in the 1st stage, 13.2Ϯ1.7 in the 2nd stage and 14.9Ϯ2.2 in the 3rd stage in pedaling and 9.8Ϯ1.6 in the 1st stage, 11.3Ϯ1.1 in the 2nd stage and 12.2Ϯ1.0 in the 3rd stage for running. Boutcher et al (1989) observed that RPE at LT were from 9.0Ϯ2.6 to 10.6Ϯ3.0 in pedaling and from 10.4Ϯ2.4 to 12.0Ϯ3.7 during running for males. Purvis and Cureton (1981) reported that RPE at the ventilatory threshold (VT) was 14.2Ϯ0.9 for males during pedaling.…”
Section: Discussionmentioning
confidence: 86%
“…It is known that RPE is actually more strongly coupled with blood lactic acid accumulation thresholds than with %HRmax or %VO 2 max. [31][32][33][34][35][36] The more highly trained individual will work to a greater proportion of HRmax or VO 2 max for a given blood lactate but the RPE at this given blood lactate will be the same in the trained and less trained individual.…”
Section: Rpe and %Vo 2 Maxmentioning
confidence: 99%
“…The relationships between pairs of variables were analyzed by a Pearson product moment test and completed by a cor-_____________________________________________________________ HOW LONG WOULD YOU BE ABLE TO PERFORM AN EXERCISE AT THIS INTENSITY TO EXHAUSTION ? _____________________________________________________________ 20 19 2 minutes 18 17 4 minutes 16 15 8 minutes 14 13 15 minutes 12 11 30 minutes 10 9…”
Section: Discussionmentioning
confidence: 99%